DETERMINAN KEJADIAN INFEKSI SALURAN PERNAPASAN AKUT (ISPA) PADA PEKERJA DI PT INDONESIA POWER UNIT PLTU BANTEN 3 LONTAR OMU - Sania Izel Askia (2023)
Based on data from the occupational health clinic, the most common disease encountered at PT Indonesia Power Unit PLTU Banten 3 Lontar OMU was Acute Respiratory Infection (ARI). The purpose of this study was to determine factors associated with the incidence of ARI among workers. This research was an analytic survey with a cross-sectional design. A total of 66 workers were selected as samples by using a purposive sampling technique. A questionnaire and Air Quality Index Monitor were used as instruments to collect data. Data were analysed by using a Chi-Square test and logistic regression prediction models. The results showed that there was a relationship between age (p-value=0.019) and knowledge (p-value 0.049) while there was no relationship between education (p-value=0.079), years of service (p-value=0.148), smoking habits (p-value 1.000), the use of PPE (p-value=0.070) and exposure to dust (p-value=0.063) with the incidence of ARI. The most dominant variable related to the incidence of ARI was knowledge (PR=4.386). Knowledge sharing should be held from the company to workers regarding the definition, causes and ways to prevent ISPA because ISPA is the most common health problem found in workers at PT Indonesia Power Unit PLTU Banten 3 Lontar OMU.